The approximation problems of solutions of the compressible fluid flow in an exterior domain - Teresė Leonavičienė (Lietuvos Matematikos Rinkinys)
The approximation of solutions of the three-dimensional steady compressible flow (linearized problem) in an exterior domain is studied. The formal error estimates are obtained.